Ghost Dance - Mullenneaux, Lisa (Radical Teacher, 2019)
My poem draws on two threads of American history in the West, contact of indigenous peoples with European immigrants and the experience of workers at the Nevada Nuclear Bomb Site during the 1950s and ’60s. In my mind, the decimation of the native population and confiscation of their land paved the way for bomb-building experiments that poisoned thousands of government workers and residents. Two oral histories, Native American Testimonies and American Ground Zero, informed my understanding of these events.